Greece : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
The staff report for the 2004 Article IV Consultation on Greece focuses on economic developments and policies. Rising incomes and a falling, though still high, unemployment rate underpinned strong household consumption, while increased profitability spurred investment spending, especially construction. Inflation has been above the euro area average, eroding international competitiveness and export market shares. Regarding structural policy, the authorities recognized that Greece still lags significantly behind the European Union in real per capita income despite the economic boom.